Preparation of Speeded Action as a Psychophysiological Concept. (article). - Jennings, Richard J.
Mental preparation aids performance and induces multiple psyshiological changes that should inform concepts of preparation. To date, however, these changes have been interpreted as being due to global preparatory process (e. g., attention or alertness). The authors review pschophysiological and performance investigation of preparation. Concept of the central regulation of action offer an integrative framework for understanding the psychophysiology of preparation. If people process multiple streams of information concurrently , then preparatory processing requires a form of supervisory attention-central regulation to maintain unity of action. This concept is consistent with existing psychophysiological results and link them to current information processing . Conversely, psychophysiological measures may provide indicates to test concepts within theories of the central regulation of action. -- (from the author)